Immediate or early skin‐to‐skin contact after a Caesarean section: a review of the literature - Stevens, Jeni (Matern Child Nutr, 2014)
The World Health Organization and the United Nations International Children's Emergency Fund recommends that mothers and newborns have skin‐to‐skin contact immediately after a vaginal birth, and as soon as the mother is alert and responsive after a Caesarean section. Skin‐to‐skin contact can be defined as placing a naked infant onto the bare chest of the mother. Caesarean birth is known to reduce initiation of breastfeeding, increase the length of time before the first breastfeed, reduce the incidence of exclusive breastfeeding, significantly delay the onset of lactation and increase the likelihood of supplementation. The aim of this review is to evaluate evidence on the facilitation of immediate (within minutes) or early (within 1 h) skin‐to‐skin contact following Caesarean section for healthy mothers and their healthy term newborns, and identify facilitators, barriers and associated maternal and newborn outcomes. A range of electronic databases were searched for papers reporting research findings published in English between January 2003 and October 2013. Seven papers met the criteria. This review has provided some evidence that with appropriate collaboration skin‐to‐skin contact during Caesarean surgery can be implemented. Further evidence was provided, albeit limited, that immediate or early skin‐to‐skin contact after a Caesarean section may increase breastfeeding initiation, decrease time to the first breastfeed, reduce formula supplementation in hospital, increase bonding and maternal satisfaction, maintain the temperature of newborns and reduce newborn stress.